Efisiensi Heat Exchanger (HE-002) Pada Crude Distillation Unit di Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi (PPSDM Migas) - Cassanova Istiqomah Walhawanadana; Haidar Luthfi Amrullah (Jurnal Nasional Pengelolaan Energi MigasZoom, 2022)
PPSDM Migas Cepu processes crude oil from PT. Pertamina EP Asset 4 Cepu Field becomes Pertasol CA, Pertasol CB, Pertasol CC, Solar and Residue, through the Crude Distillation Unit (CDU) process in the refinery unit. In the early stages of the process, the raw material in the form of crude oil is heated in a heat exchanger and then reheated in the furnace until it reaches a certain temperature to flow to the next stages. A heat exchanger is a heat transfer device between a hot fluid and a cold fluid, without the need to mix the two fluids. HE-002 shell and tube type is one of five heat exchanger units owned by the PPSDM Migas Refinery unit. HE-002 plays a role in heating the cold fluid in the form of crude oil which is placed in the tube and flows the hot fluid in the form of diesel fuel through the shell. Heat transfer can occur due to temperature differences between fluids. However, in actual conditions, the amount of heat released by diesel and the heat received by crude oil is not of the same value. This study aims to determine the heat transfer efficiency on the HE-002 by comparing the heat changes in the hot fluid and cold fluid. After data collection and calculations, the efficiency of the HE-002 PPSDM Migas Refinery unit was 94.463% with a heat loss percentage of 4.753%.